Relevance of Aromatase Inhibitors in Breast Cancer Treatment - Sood, Ankita; Lang, Damanpreet K.; Kaur, Rajwinder; Saini, Balraj; Arora, Sandeep (Current Topics in Medicinal Chemistry, 2021)
Efficacious treatment for breast cancer is still a challenge despite the presence of various treatment options. Aromatase enzyme present in the breast tissue is responsible for estrogen formation from androgens. Aromatase inhibitors manifest remarkably ameliorated therapeutic efficacy as compared to the current therapeutic options available and exhibit a better safety profile as compared to the other drugs. Clinical resistance to aromatase inhibitors is perceived as a lack of growth inhibition by aromatase inhibitors treatment and cancer therapy becomes ineffective in causing a decrease in the size of the tumor. Naturally extracted aromatase inhibitors have a huge positive impact on vitality and living standards. This review article highlights the particulars of the currently approved steroidal and non-steroidal aromatase inhibitors for clinical use, adverse effects associated with their use and approach to tackling the problem, various strategies to overcome aromatase inhibitors resistance, information on the synthesis of various peculiar aromatase inhibitors which can prove as highly efficient and potent drugs in the near future and the drugs of natural and semi-synthetic origin which can demonstrate to be more efficient, potent and less-toxic than conventional therapy.
Keywords: Aromatase